Evaluation and regulation of non‐indigenous macro‐organisms: experience in France1. (19th July 2016) - Reynaud, P.; Gautier, B.
Abstract : Following the entry into force of French Decree 2012‐140, published on 30 January 2012, concerning authorization of the entry to French territory and introduction into the environment of non‐indigenous macro‐organisms (beneficial, including pollinators and biological control agents) useful for crops, the French Agency for Food, Environmental and Occupational Health and Safety (ANSES) is in charge of the assessment of applications for authorization submitted by petitioners. This article presents some relevant definitions and briefly describes the process of evaluation and authorization of non‐indigenous macro‐organisms in France. It also summarizes the data requirements for application for import of non‐indigenous macro‐organisms for use under containment conditions or for introduction of non‐indigenous macro‐organisms into the environment.